Identity, language socialization, and family language policies in dialect contact: the case of Argentinean immigrants in Malaga, Spain - von Essen María Clara (Journal of World Languages, 2023)
This paper explores from a qualitative and quantitative approach, the complex interactions between second dialect accommodation or acquisition, language socialization, ideologies, family language policies, and identity, among Argentinean immigrants living in Malaga, Spain (n = 72). We found that family language policies – and more specifically mothers’ language policies and their stances towards both varieties in contact – shape their children’s development, connect with their formal school success, determine D1 maintenance, and even affect identity projection. We also found discrepancies between conservative family language policies and linguistic production: what families try to do with language does not always match their own linguistic performance. Through the analysis of different language components – phonological, morpho-syntactic, and lexical – we conclude that linguistic accommodation or second dialect acquisition does not always follow a linear path to assimilation, but it is related to early stages of exposure and formal education in the D2 community (optimal age acquisition period), takes place to improve mutual intelligibility, derives from both unconscious and conscious decisions to change D1, and allows speakers to showcase different identities through accommodation or divergence.